Time to stop polishing the brass on the Titanic: moving beyond 'quick-and-dirty' teacher education for inclusion, towards sustainable theories of change. Issue 7 (3rd August 2019) - Lewis, Ingrid; Corcoran, Su Lyn; Juma, Said; Kaplan, Ian; Little, Duncan; Pinnock, Helen
ABSTRACT: Interest in inclusive education in the global south has grown significantly since the adoption of the Salamanca Statement in 1994. Increasingly, those who fund and provide education want to be seen taking action on inclusion generally and disability inclusion specifically. However, the much-welcomed enthusiasm to respond to global commitments is not always matched with the necessary expertise and commitment to longer-term action and change. The growth in inclusive education policies and pilot projects in the last decade is hard to miss, but changes resulting from these interventions are often less apparent. Why is that? Drawing on the Enabling Education Network's 22 years of experience as a global inclusive education network and consultancy provider, we present alternative pathways for change in teacher education for inclusion. We stress that change in teaching practice remains limited not because inclusive education is a fundamentally flawed concept, but because too much focus is given to 'quick-and-dirty' trainings that quickly yield donor-pleasing statistics and publicity-attracting case studies, but fail to elicit sufficiently extensive and sustainable change to education systems and cultures.